Development of Nahwu Learning Module for Students of Madrasah Diniyah Wali Songo Sukajadi Lampung| Pengembangan Modul Pembelajaran Nahwu untuk Peserta Didik Madrasah Diniyah Wali Songo Sukajadi Lampung - Jauharotun Nafisah; Koderi; Muhamad Akmansyah; Erlina; Ahmad Mukhlishin (Mantiqu Tayr: Journal of Arabic Language, 2023)
The development of nahwu learning modules for madrasah diniyah students aims to produce nahwu learning module products for madrasah diniyah students, find out the level of feasibility of nahwu learning module products for madrasah diniyah students, and find out how effective the use of nahwu learning module products for madrasah diniyah students. The research method uses research and development methods. This development research refers to the steps used in the development model described by Dick and Carey which has revision activities ranging from 1) Identifying general learning objectives, 2) Carrying out learning analysis, 3) Identifying behavior 4) Formulating performance objectives, 5) Develop test items, 6) Develop learning strategies, 7) Develop and select learning materials, 8) Design and carry out formative evaluations, 9) Revise learning materials. Data collection using assessment sheets, response questionnaires, and learning outcomes tests. The data analysis technique uses paired sample t-test with a significance level of 0.05. The results of this research are in the form of nahwu learning modules for Madrasah Diniyah students which can be an easy solution in understanding nahwu science. Module feasibility is obtained from the validation results of design experts and learning material experts with very feasible criteria. The effectiveness rate of the module was obtained from a small group trial of 90% with a very good response, Medium group trials were 95% with very good responses, and large group trials were 95% with very good responses. It can be concluded that this module has a very positive effect on the nahwu learning process for Madrasah Diniyah students.